Doing without : women and work after welfare reform - Henrici, Jane (University of Arizona Press, 2006)
"In Doing Without, Jane Henrici brings together nine contributions to tell the story of welfare reform from inside the lives of the women who live with it. Cases from Chicago and Boston are combined with a focus on San Antonio from one of the largest multi-city investigations of welfare reform ever undertaken. The contributors argue that the employment opportunities available to poorer women, particularly single mothers and ethnic minorities, are insufficient to lift their families out of poverty. Typically marked by variable hours, inadequate wages, and short-term assignments, both employment and training programs fail to provide stability or the kinds of benefits - such as health insurance, sick days, and child care options - that are necessary to sustain both work and family life." "The chapters also examine the challenges facing the women who seek assistance and those who work in public and private agencies to provide it as they navigate ever-changing requirements and regulations, decipher alterations in Medicaid, and apply for training and education. Contributors urge the nation to repair the social safety net for women in transition and offer genuine access to jobs with wages that actually meet the cost of living."--Jacket